2018
DOI: 10.4162/nrp.2018.12.6.512
|View full text |Cite
|
Sign up to set email alerts
|

Complementary feeding practices and nutritional status of children 6–23 months old: formative study in Aceh, Indonesia

Abstract: BACKGROUND/OBJECTIVESThe 6–23 months for infants is the longest period in the “first 1,000 days” of life. This period is very important for child development, so complementary feeding (CF) practices should be optimized to maximize children's potential for growth and development. The aim of this study was to analyze the CF practices and nutritional status of children aged 6–23 months.SUBJECTS/METHODSFor this cross-sectional study, 392 children aged 6–23 months were selected using stratified random sampling. Soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
46
4
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 16 publications
13
46
4
6
Order By: Relevance
“…Results of this study pertaining to mother's role and knowledge on the nutritional status of infant and toddler feeding are consistent with those of other studies that found no significant association between maternal nutrition knowledge and stunting, but not wasting in Indonesia (Webb & Block, 2003;Webb & Block, 2004). On the contrary, other studies found significant association between mother's feeding knowledge and nutritional status of their children (Siagian & Halisitijayani, 2014;Sukandar et al, 2015;Hadju et al, 2016;Masthalina & Agustina, 2017;Ahmad et al, 2018) and the study of Appoh and Krekling (2005) in Ghana found the positive association between mother's nutrition knowledge and underweight, which measures both stunting and wasting. Mothers with above primary level education can significantly reduce stunting and wasting in children.…”
Section: Mother's Knowledgesupporting
confidence: 89%
“…Results of this study pertaining to mother's role and knowledge on the nutritional status of infant and toddler feeding are consistent with those of other studies that found no significant association between maternal nutrition knowledge and stunting, but not wasting in Indonesia (Webb & Block, 2003;Webb & Block, 2004). On the contrary, other studies found significant association between mother's feeding knowledge and nutritional status of their children (Siagian & Halisitijayani, 2014;Sukandar et al, 2015;Hadju et al, 2016;Masthalina & Agustina, 2017;Ahmad et al, 2018) and the study of Appoh and Krekling (2005) in Ghana found the positive association between mother's nutrition knowledge and underweight, which measures both stunting and wasting. Mothers with above primary level education can significantly reduce stunting and wasting in children.…”
Section: Mother's Knowledgesupporting
confidence: 89%
“…This findings of study showed that wasting was more likely among children who were not recommended minimum meal frequency as compared to child who got recommended MMF among Dalit. This findings got supported from the result of Ethiopia [47] and Indonesia [35]. This study revealed that about one-fourth of the Dalit child mother were daily wages/labour.…”
Section: Discussionsupporting
confidence: 69%
“…Similarly, the findings showed that the underweight was also protected among 6-11 months as compared to 12-23 months in Dalit. The findings got supported from the study of Pakistan [17], Indonesia [35]. Undernutrition is less among children younger than six months because child nutrition depends upon the breastfeeding [36].…”
Section: Discussionmentioning
confidence: 65%
“…In the study result of Udoh and Amodu, there was a signi cant association (p<0.05) between introduction of CF at six months old with wasting, the MDD was signi cantly associated with underweight and similarly, MAD was signi cantly associated with underweight too. Also, this study showed signi cant association between stunting and MMF, MDD and MAD [17].…”
Section: Discussionsupporting
confidence: 62%
“…Saaka et al study presented signi cant positive association between introduction of CF at six months old and higher height for age z-score [18] but our study showed there is no association between introduction of CF at six months old and length for age z-score (stunting). In Ahmad et al study there was no association on indicators of CF, namely MMF, MDD, MAD and timely introduction to CF with wasting, underweight and stunting [17]. Kimiywe et al found that CF practices were signi cantly correlated with nutritional status, particularly MDD [19].…”
Section: Discussionmentioning
confidence: 96%